The Light promotes in vitro bulbing of Sprekelia formosissima - Uribe-Treviño, Agustín; Pedraza-Santos, Martha Elena; Delgado-Valerio, Patricia; Martínez-Palacios, Alejandro; González Hernández, Juan Carlos; Antonio-López, Pedro (Revista Mexicana de Ciencias Agrícolas, 2024)
Sprekelia formosissima is an ornamental geophyte that is propagated by bulb division since it takes up to four years to obtain it by seed. Micropropagation is an option to produce bulbs that grow and accumulate carbohydrates in a differentiated way under different light conditions and depending on the species. In 2022, the in vitro growth of S. formosissima bulbs with 0, 30, 60, 120, and 130 μmol m-2 s-1 of light was evaluated. The bulbs were grown in MS medium with 4% sucrose and a photoperiod of 16 h. At 80 days, number, color, chlorophyll and length of leaves, fresh and dry weight of leaves and bulbs, and width and length of bulbs were measured. Total soluble sugars, reducing sugars, sucrose, fructose in leaves and starch in bulbs were evaluated. To determine starch, 4 and 8 U of amyloglucosidase and α-amylase were tested, with 6, 12 and 24 h of digestion. The data were used to perform an Anova and a Tukey test (p< 0.05). With 130 μmol m-2 s-1, the fresh and dry weight and diameter of the bulb, number of leaves, starch in bulbs, and chlorophyll a, b and total increased by 152, 433, 44, 87, and 251% and 55, 35, and 58 times, respectively, compared to the data recorded in the dark. The high intensity of light in vitro increases the biomass and starch in S. formosissima bulbs, which was estimated with 8 U of amyloglucosidase and α-amylase and 24 h of digestion.
Keywords: geophytes micropropagation; light intensity; carbohydrates